Efek Sinbiotik Jamur Tiram Teraktivasi UVB dan Air Kelapa Muda terhadap Integritas Kolon dan Survival Tikus Kolitis - Dian Rudy Yana; Shendy Meian Nimas Nurinda; Atina Hussaana; Siti Thomas Zulaikhah; Conita Yuniarifa (Jurnal Anestesi, 2026)
Colitis is an inflammatory disorder of the colon characterized by disruption of immune homeostasis and damage to the intestinal mucosa. Synbiotics play an important role in immune regulation, while UVB-activated oyster mushroom (Pleurotus ostreatus) is a potential source of vitamin D2 with anti-inflammatory properties. The combination of these components with young coconut water may offer a beneficial approach to ameliorating colitis. This study aimed to investigate the effects of Debiococo, a combination of UVB-activated oyster mushroom powder, probiotics, and young coconut water, on colitis symptoms, colonic mucosal integrity, and survival rate in rats with acetic acid-induced colitis. This experimental study used a posttest-only control group design involving 30 male Wistar rats randomly divided into five groups: normal control, negative control, positive control treated with sulfasalazine, Debiococo dose 1, and Debiococo dose 2. Colitis was induced through intrarectal administration of 4% acetic acid, followed by treatment for eight days. The observed parameters included colitis symptoms, goblet cell count, and survival rate. The results showed significant differences in goblet cell counts among groups (p < 0.001), with Debiococo dose 2 producing goblet cell counts comparable to those of the normal control group. In addition, Debiococo dose 2 maintained the survival of all experimental animals until the end of the observation period and achieved the highest survival rate among the colitis groups. These findings indicate that Debiococo has potential as a synbiotic-based adjunct therapy for maintaining colonic mucosal integrity and improving survival outcomes in colitis conditions.